Symbolism of the Sun in the Sacral Monuments of Armenians and Lithuanians - Zabulytė, Jolanta (Acta Orientalia Vilnensia, 2003)
Armenian and Lithuanian sacral monuments that follow the Christian tradition seem to have nothing in common at the first sight: khachkars - stone stelas (khach - ‘cross’, kar - ‘stone’) originated in the 4th-5th centuries, their traditional schemes have formed in the 11th-12th centuries and they were spreading until 16th-17th centuries; meanwhile Lithuanian wooden crosses in terms of origin are most recent (18th c.) and are characteristic of their variety of architectonics and decor motives. Nevertheless, this difference is only formal, i.e. stylistic, because their originality, like the one of Celtic crosses, was predetermined by religious syncretism when in certain cases gods, images and symbols of the old religion were ‘covered’ and in other cases - adapted to the iconographic system of the new religion. Influences of the archaic religion reveal in various aspects. However, this paper focuses only on motives related to the symbolism of the Sun. After a short review on the symbolism of the decor of Armenian monuments, a conclusion is drawn that Christian khachkars are dominated by the motives of solar cult related to the heavenly god-king that go back to the times of ancient Iran. Cross-of the tree of Life, wings of god-king with the sun that later became rosette, radiant faces or celestial bodies on animals and likely solar mythical gods-heroes can be interpreted as different models that express the aspects of sun-related Divine Life. These models have notional equivalents in Christian iconography, i.e. in the themes of Christ-King of the World, Sol Invictus, Christ’s Sacrifice and Resurrection. Since the Armenian world-view was mostly influenced by Iranian religious images, the occurrence of cross wings that are absent in other Christian countries are also related to the Old Iranian religion. The wings of the solar circle in the emblem of the supreme god Ahura Mazda (Armenian Aramazda) remained as equivalents of the God’s son and king and the sun of faith that express also the aspects of the divine safety and worship in Christian iconography. Lithuanian wooden crosses bearing the form of sun-circle and sun-rose as well as festoon belong to the world-view of rural people. It maintains singular features and it could have originated under the influence of former compositions of apexes-suns on wooden roofed pillars. However, possible impact of the forms of liturgical utensils (monstrances) and sacred attributes (aureoles) should not be rejected either. Local features undoubtedly include the rays of vegetal shape that form the solar circle and are related to the concept of posthumous heaven - gardens of the sun and souls-flowers within it. The decor of wooden crosses often contains 2, 7 or 9 suns that express not only the ideas of God, the light of faith, but also safety and worship of the sun (Christ) in regard to the soul of the dead that travel to the eternal abode. Today it is hard to make a clear distinction where the influence of images of the old world-view end up and the ‘territory’ that belongs to the Christian iconography starts. It is difficult to attribute unambiguously the appearance and popularity of solar motives in the compositions of crosses to one or another religion. Consequently, it is possible to assume that these symbolic systems merged as coequal on the same plane of the sacred where the Sun and Life shine in the most vivid colors within the context of the Divine Existence.